Interindividual Variability in Hepatic Organic Anion-Transporting Polypeptides and P-Glycoprotein (ABCB1) Protein Expression: Quantification by Liquid Chromatography Tandem Mass Spectroscopy and Influence of Genotype, Age, and Sex - Prasad, Bhagwat; Evers, Raymond; Gupta, Anshul; Hop, Cornelis E. C. A; Salphati, Laurent; Shukla, Suneet; Ambudkar, Suresh V; Unadkat, Jashvant D (Drug metabolism and disposition, 2014)
Interindividual variability in protein expression of organic anion-transporting polypeptides (OATPs) OATP1B1, OATP1B3, OATP2B1, and multidrug resistance-linked P-glycoprotein (P-gp) or ABCB1 was quantified in frozen human livers (n = 64) and cryopreserved human hepatocytes (n = 12) by a validated liquid chromatography tandem mass spectroscopy (LC-MS/MS) method. Membrane isolation, sample workup, and LC-MS/MS analyses were as described before by our laboratory. Briefly, total native membrane proteins, isolated from the liver tissue and cryopreserved hepatocytes, were trypsin digested and quantified by LC-MS/MS using signature peptide(s) unique to each transporter. The mean ± S.D. (maximum/minimum range in parentheses) protein expression (fmol/µg of membrane protein) in human liver tissue was OATP1B1- 2.0 ± 0.9 (7), OATP1B3- 1.1 ± 0.5 (8), OATP2B1- 1 1.7 ± 0.6 (5), and P-gp- 0.4 ± 0.2 (8). Transporter expression in the liver tissue was comparable to that in the cryopreserved hepatocytes. Most important is that livers with SLCO1B1 (encoding OATP1B1) haplotypes *14/*14 and *14/*1a [i.e., representing single nucleotide polymorphisms (SNPs), c.388A > G, and c.463C > A] had significantly higher (P < 0.0001) protein expression than the reference haplotype (*1a/*1a). Based on these genotype-dependent protein expression data, we predicted (using Simcyp) an up to ∼40% decrease in the mean area under the curve of rosuvastatin or repaglinide in subjects harboring these variant alleles compared with those harboring the reference alleles. SLCO1B3 (encoding OATP1B3) SNPs did not significantly affect protein expression. Age and sex were not associated with transporter protein expression. These data will facilitate the prediction of population-based human transporter-mediated drug disposition, drug-drug interactions, and interindividual variability through physiologically based pharmacokinetic modeling.